Analisis Kinerja Keuangan Bank Syariah Indonesia (BSI) Sebelum dan Setelah Merger - Alvina Dea Nurita; Dian Kusumaningrum; Nova Maulud Widodo (Equivalent : Journal of Economic, Accounting and Management, 2026)
Abstract : Merger was expected to improve the company’s financial performance. However, following the merger, a ransomware attack by the LockBit group targeted BSI's services, causing disruptions to banking operations and the loss of a substantial amount of customer data. Incident is suspected to have resulted from issues arising during the merger, particularly challenges in the account and system migration process. The purpose of this study is to determine whether there are differences in risk profile, profitability, and capital before and after the merger. The population used in this study consists of 13 Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK). The sample includes 4 banks selected through purposive sampling. The study utilizes secondary data, with data collection techniques including literature review and documentation. The variables compared are risk profile, profitability, and capital. The data analysis techniques employed include descriptive statistical analysis, normality testing, and the paired sample t-test. The software used for data processing in this study is SPSS version 22. The results of this study indicate that there are partial statistical differences in the risk profile and capital before and after the merger. However, profitability shows a statistically significant difference before and after the merger. Abstrak : Merger diharapkan dapat meningkatkan kinerja keuangan perusahaan. Namun, setelah merger terjadi penyerangan oleh group ransomware LockBit pada BSI yang menyebabkan layanan bank terganggu dan banyaknya data nasabah yang hilang. Hal ini diduga terjadi akibat dampak merger yang menyebabkan kendala dalam proses migrasi rekening dan sistem. Tujuan penelitian ini adalah untuk mengetahui apakah ada perbedaan pada profil risiko, rentabilitas, dan permodalan sebelum dan setelah merger. Populasi yang digunakan adalah Bank Umum Syariah (BUS) yang terdaftar di Otoritas Jasa Keuangan (OJK) sebanyak 13 perusahaan. Jumlah sampel yang digunakan sebanyak 4 perusahaan dengan metode purposive sampling. Data penelitian menggunakan data sekunder dengan teknik pengumpulan data studi pustaka dan dokumentasi. Variabel yang dibandingkan adalah profil risiko, rentabilitas dan permodalan. Teknik analisis data yang digunakan adalah analisis statistik deskriptif, uji normalitas, dan uji paired sample t-Test. Alat bantu software yang digunakan dalam penelitian ini adalah SPSS versi 22. Hasil dari penelitian ini menunjukkan bahwa profil risiko dan permodalan secara statistik terdapat perbedaan sebagian sebelum dan setelah merger. Namun, pada rentabilitas terdapat perbedaan yang signifikan secara statistik sebelum dan setelah dilakukan merger.